2020
DOI: 10.1021/acs.oprd.0c00485
|View full text |Cite
|
Sign up to set email alerts
|

Scalable On-Demand Production of Purified Diazomethane Suitable for Sensitive Catalytic Reactions

Abstract: We have developed a convenient development-scale reactor (0.44 mol/h) to prepare diazomethane from N-methyl-N-nitroso-p-toluenesulfonamide (MNTS) in ∼80% yield. Diazomethane (CH 2 N 2 ) made with this reactor is extracted into nitrogen gas from the liquid reaction mixture, effectively removing it from reagents and byproducts that may interfere in subsequent reactions. Vertically oriented tubular reactors were used to produce and consume diazomethane in situ. Key features of this reactor include high productivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Because of the need for a specialized plant to operate this diazomethane process safely, we always had envisioned that this reaction would be converted to a continuous flow process. Early experiments using a continuous diazomethane generator were encouraging but were plagued with significant clogging issues arising from the formation of polymethylene polymer side products . These observations were consistent with the requirement for ∼8 equiv of diazomethane in the batch process, i.e., much of the active carbene reagent was being consumed by reaction with itself.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the need for a specialized plant to operate this diazomethane process safely, we always had envisioned that this reaction would be converted to a continuous flow process. Early experiments using a continuous diazomethane generator were encouraging but were plagued with significant clogging issues arising from the formation of polymethylene polymer side products . These observations were consistent with the requirement for ∼8 equiv of diazomethane in the batch process, i.e., much of the active carbene reagent was being consumed by reaction with itself.…”
Section: Resultsmentioning
confidence: 99%
“…The rhodium-catalyzed reactions of diazo compounds have broad applications in organic synthesis. Previously, we showed that donor/acceptor carbenes offer new synthetic opportunities because of the attenuating influence of the donor group. , They can be used in several different types of enantioselective transformations, such as cyclopropanation, cyclopropenation, C–H and X–H insertions, as well as a variety of reactions involving ylide intermediates. , In the past, questions arose about the feasibility of running large-scale reactions with diazo compounds because they are highly energetic and potentially unstable. These safety concerns have been greatly alleviated in recent years on account of the advances in generating diazo compounds in flow. Considerable efforts have been made to replace the rhodium with cheaper metals, but the dirhodium catalysts have special properties that are difficult to replicate. , They are kinetically very active at decomposing diazo compounds, yet perfectly stable to air and moisture. Many of the designed chiral ligands self-assemble around the dirhodium core to generate elaborate high-symmetry chiral complexes capable of very high levels of asymmetric induction .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, flow synthesis may afford access to a greater scope of diazo compounds, including less stable reagents . Previous literature has achieved diazo synthesis in flow via diazo transfer using tosyl azide, , diazotization of primary amines, hydrazone fragmentation, and base-catalyzed elimination of diazald. However, each of these methodologies generates stoichiometric byproducts and requires large amounts of an aqueous base, which may lead to diazo decomposition or undesired reactivity causing interference with downstream reactions, thus requiring in-line separation. In contrast, hydrazone oxidation offers a milder method to generate diazo compounds with water as a benign byproduct, without requiring additional separation steps.…”
Section: Introductionmentioning
confidence: 99%